Health literacy and health behaviors among adults with prediabetes, 2016 behavioral risk factor surveillance system - Luo, Huabin; Chen, Zhuo; Bell, Ronny; Rafferty, Ann P.; Gaskins Little, N. Ruth; Winterbauer, Nancy (2020)
Objectives: Evidence is needed for designing interventions to address health literacy–related issues among adults with prediabetes to reduce their risk of developing type 2 diabetes. This study assessed health literacy and behaviors among US adults with prediabetes and the mediating role of health literacy on health behaviors. Methods: We used data from the 2016 Behavioral Risk Factor Surveillance System (BRFSS) (N = 54 344 adults). The BRFSS health literacy module included 3 questions on levels of difficulty in obtaining information, understanding health care providers, and comprehending written information. We defined low health literacy as a response of “somewhat difficult” or “very difficult” to at least 1 of these 3 questions. Respondents self-reported their prediabetes status. We included 3 health behavior indicators available in the BRFSS survey—current smoking, physical inactivity, and inadequate sleep, all measured as binary outcomes (yes/no). We used a path analysis to examine pathways among prediabetes, health literacy, and health behaviors. Results: About 1 in 5 (19.0%) adults with prediabetes had low health literacy. The rates of physical inactivity (31.0% vs 24.6%, P <.001) and inadequate sleep (38.8% vs 33.5%, P <.001) among adults with prediabetes were significantly higher than among adults without prediabetes. The path analysis showed a significant direct effect of prediabetes and health literacy on health behaviors. The indirect effect of prediabetes through health literacy on health behaviors was also significant. Conclusion: BRFSS data from 2016 showed that rates of low health literacy and unhealthy behaviors were higher among adults with prediabetes than among adults without prediabetes. Interventions are needed to assist adults with prediabetes in comprehending, communicating about, and managing health issues to reduce the risk of type 2 diabetes. © 2020, Association of Schools and Programs of Public Health.